PEMANFAATAN KULIT BUAH KAKAO (Theobrama cacao L.) FERMENTASI DENGAN CAIRAN RUMEN TERHADAP KONSUMSI DAN KECERNAAN BAHAN KERING DAN BAHAN ORGANIK PADA SAPI PERANAKAN ONGOLE (PO) - Wira Sitanggang (Jurnal Peternakan Integratif, 2012)
Abstrac: Fermented cacao pod wit rumen fluid can be increase the comsumtion and digestibility of dry mater and organic mater. The objective of this research to determine the effect of various level of cacao Fruit Leather (Theobrama cacao L.). Fermented with rumen fluid in concentrate on feed comsumption an digestibility of dry matter and organic material in ongole crossbred cattle. The design used in this study is Latin Square Design (LSD) with 4 treatments. The treatments consist of PO (without cacao pod fermented); P1 (10% cacao pod fermented in concentrate); P2 (20% cacao pod fermented in concentrate). The result of this research showed that the average dry matter consumption (kg/head/day) 7.78; 7.83; 7.95; and 7.87, respectively. Average consumption of organic matter (kg/head/day) 7.43; 7.38; 7.51; 7.44. Average dry matter digestibility 67.59; 66.73; 67.52; and 66.68. Average organic matter digestibility 66.57; 65.94; 66.27; and 65.77. Statiscally shows that the utilization of cacao pod fermented with rumen fluid  not significantly different (P>0.05) on dry matter intake, consumption of organic matter, dry matter digestibility and organic matter digestibility of ongole crossbred. The conclution of this research that utilization of cacao pod fermented by rumen fluid can be giving  on ongole cattle crossbred. Keywords: Cacao Pod, Fermentation, Rumen Fluid, Ongole Cattle Crossbred